Identification and Regulation of Active Sites on Nanodiamonds: Establishing a Highly Efficient Catalytic System for Oxidation of Organic Contaminants - Shao, P.; Tian, J.; Yang, F.; Duan, Xiaoguang; Gao, S.; Shi, W.; Luo, X.; Cui, F.; Luo, S.; Wang, Shaobin (Wiley, 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim. Nanodiamonds exhibit great potential as green catalysts for remediation of organic contaminants. However, the specific active site and corresponding oxidative mechanism are unclear, which retard further developments of high-performance catalysts. Here, an annealing strategy is developed to accurately regulate the content of ketonic carbonyl groups on nanodiamonds; meanwhile other structural characteristics of nanodiamonds remain almost unchanged. The well-defined nanodiamonds with well-controlled ketonic carbonyl groups exhibit excellent catalytic activity in activation of peroxymonosulfate for oxidation of organic pollutants. Based on the semi-quantitative and quantitative correlations of ketonic carbonyl groups and the reaction rate constants, it is conclusively determined that ketonic carbonyl groups are the catalytically active sites. Different from conventional oxidative systems, reactive oxygen species in nanodiamonds at peroxymonosulfate system are revealed to be singlet oxygen with high selectivity, which can effectively oxidize and mineralize the target contaminants. Impressively, the singlet-oxygen-mediated oxidation system significantly outperforms the classical radicals-based oxidation system in remediation of actual wastewater. This work not only provides a valuable insight for the design of new nanocarbon catalysts with abundant active sites but also establishes a very promising catalytic oxidation system for the green remediation of actual contaminated water.